[2]Pseudorotaxane‐Based Supramolecular Optical Indicator for the Visual Detection of Cellular Cyanide Excretion. Issue 63 (16th October 2019) - Zhou, Jiong; Yu, Guocan; Li, Yang; Shen, Jie; Wang, Mengbin; Li, Zhengtao; Wei, Peifa; Tang, Jianbin; Huang, Feihe
Abstract: Cyanide is extremely hazardous to living organisms and the environment. Owing to its wide range of applications and high toxicity, the development of functional materials for cyanide detection and sensing is highly desirable. Host–guest complexation between bis( p ‐phenylene)‐34‐crown‐10 H and N ‐methylacridinium salt G remarkably decreases the detection limit for cyanide anions compared with that of the guest itself. The [2]pseudorotaxane selectively recognizes the cyanide anion with high optical sensitivity as a result of the nucleophilic addition of the cyanide anion at the 9‐position of G . The host–guest complexation is further incorporated into supramolecular materials for the visual detection of cyanide anions, especially the detection of cellular cyanide excretion with a detection limit of 0.6 μm . This supramolecular method provides an extremely distinct strategy for the visual detection of cyanide anions. Abstract : Detecting cyanide : Host–guest complexation between bis( p ‐phenylene)‐34‐crown‐10 and N ‐methylacridinium salt is studied in both solution and the solid state. This host–guest complexation is responsive to CN − . The [2]pseudorotaxane is used in the visual detection of cellular cyanide anion excretion with a detection limit of 0.6 μm .